(untitled) (Docentes 2.0 Journal, 2022)
Gamification as a teaching-learning technique has become very popular thanks to its benefits, such as the increase in interest and motivation on the part of students in a subject. Therefore, the objective was to know the students’ reasons and the games’ dynamics that can be implemented to retain them in the teaching-learning process. The present investigation was carried out under the quantitative paradigm of an exploratory type, and experimental design with students enrolled in the different careers offered by the Faculty of Informatics of the Autonomous University of Querétaro. A questionnaire based on the Bartle test was applied to 49 students to find out their preferences regarding the dynamics of the games. Each student’s role in the match was obtained from the instrument, the type of activities that she prefers to perform based on the dynamics of the games, and actions or factors that motivate the student. Likewise, the importance of motivation in understanding the point of view of gamification is highlighted since it is selected in different types of players or roles in the game. Every kind of player has its motivation and retention method. That must be considered when designing a virtual teaching-learning environment or gamified activity to make it successful. In conclusion, to gamify efficiently, it is essential to know our students and their motivations to retain them in the teaching process and achieve their learning.